Architectural science and the sun the poetics and pragmatics of solar design - Fajkus, Matt; Whitsett, Dason (Routledge, 2018)
Architectural Science and the Sun synthesizes physics, climate, program, and perception to provide a foundation in the principles of architectural science related to the sun: solar geometry, solar analysis and design techniques, passive design principles, and daylighting. Part analytical handbook, part inspiration source for schematic design, the content comprises a critical component of effective sustainable design. Beyond the purely technical aspects of these topics, Architectural Science and the Sun begins with the premise that great architecture goes beyond energy performance and the visual-aesthetic to engage all of the senses. Given that the stimuli to which our senses respond are physical phenomena such as light, heat, and sound, the designer must manipulate these parameters through the craft of building form and technology to create the desired qualitative experience. This book is designed to help the reader develop that skill